Numerical and Experimental Investigation of Friction Effect in Limiting Dome Height Test - Sener, Bora; Kayali, E. Sabri (AMER SOC TESTING MATERIALS, 2016)
In this study, the effect of friction in limiting dome height test was investigated numerically and experimentally. Ultra-low-carbon galvanized steel sheets were used as a test material. The thickness of the material was 1.2 mm. Limiting dome height tests were carried out by using three different lubricants, and the test was modeled with the finite-element method. Simulations were done using various friction coefficients to show the effect of friction on the limiting dome height test. It has been observed that necking/fracture area is decreasing and necking/fracture location moves toward the pole side of the material with the decline of the friction coefficient. Similar results were also obtained in the experiments.
Keywords: limiting dome height test; friction; finite-element simulation; necking; ERICHSEN TEST; SHEET METALS; LUBRICATION; COEFFICIENT; STEEL; BEHAVIOR; Materials Science